Source-Receiver Interaction for Structure-Borne Sound Sources on Floor Assemblies with Floating Toppings - Abou Hamed, Mohamed (Université d'Ottawa / University of Ottawa, 2023)
Neighbor noise has repeatedly been proven to have a detrimental effect on multi-unit residential buildings (MURBs) residents’ physical and mental health. Impact noises have been shown to cause the most indoor noise annoyance amongst residents. Moreover, lightweight assemblies are known for their general poor sound insulation and are becoming increasingly popular as an alternative to concrete and steel structures in North America and Europe. Floating toppings have been used to control impact noise, but the effect of the source-receiver interaction is often neglected when they are modelled by engineers in the industry. More research needs to be done to determine the actual influence of the source-receiver interaction on floor assemblies with floating toppings. Studying the source-receiver interaction is fundamental to tackling the issue of structure-borne noise in MURBs because it has been shown to influence the first of five factors of impact sound transmission: the power injected. The power injected into a floor due to an impact source has been shown to depend on the mechanical mobility match (or the source-receiver interaction) between the impact source and the impacted floor. However, many questions remain around the significance of the source-receiver interaction. This project investigates the significance of the source-receiver interaction for structure-borne sound sources on floor assemblies with floating toppings, and how much it varies from one source-floor combination to another.
Keywords: Impact noise; Source-receiver interaction; Floating toppings